An Heat Transfer Coefficient and Pressure Characteristics in a Copper Pipe Flow System: A Preliminary study Utilizing an EG/Water Mixture - Junaedi, Akhmad; Sukarman; Khoirudin, Khoirudin; Taufik Ulhakim, Muhammad; Lintang Azizah, Renata (Jurnal Teknik Mesin Mechanical Xplore, 2024)
This study investigates the performance of an ethylene glycol/water (EG/Water) fluid at a 40:60 volume ratio, a commonly used base fluid in heating and cooling systems. The evaluation focuses on analyzing heat transfer coefficients and pressure drops. The research adopts an experimental approach, utilizing a test section made of pure copper with an inner diameter of 16 mm, an outer diameter of 19 mm, and a length of 1500 mm. The volume ratio of EG/Water at 40:60 is an input parameter, along with varying fluid flow rates controlled by a valve, ranging from 2 to 18 liters per minute. Two tubular heaters with a combined capacity of 2000 W are attached to the copper pipe, regulated by a 3000 W voltage regulator. Electric current is measured with ammeters. The experimental results reveal that the heat transfer coefficient of the EG/Water fluid increases as the fluid flow rate rises. The highest heat transfer coefficient is achieved at 18 L/min, while the lowest is observed at 4 L/min. Pressure drop increases with higher flow rates, but this does not significantly affect the friction factor, as it undergoes a noticeable decrease while the Reynolds number increases.